An Overview of Job Satisfaction of Emergency Healthcare Providers In Northern Cyprus - Daghan Aylanç; Semra Aslay (ACHSM, 2022)
Introduction: Emergency calls are a challenging triangle that requires quick assessment, immediate action, and correct decision-making. The appropriate work environment and conditions of emergency healthcare workers result in this triangle's flawless functioning. This study aims to evaluate and overview the job satisfaction of the personnel working in emergency healthcare in Northern Cyprus. Methods: This descriptive study was conducted to evaluate the job satisfaction of the personnel working in emergency healthcare in Northern Cyprus. This research involved nurses, paramedics, and EMTs, who intervene in an emergency call. The participants' job satisfaction was evaluated by the scale developed by Güneri (2011). The scale score range was 47-235. A high score was considered as increased job satisfaction. Results: 132 personnel who work in emergency healthcare in Northern Cyprus participated in this study. 31.82% were aged between 36 and 49 years, 81.6 % were women, and 42.42% were undergraduates. 31.6% had worked for more than ten years. 39.39% (52) declared that they had occupational disease/accidents. 43.18% said they had received training more than two years ago. The participants' mean job satisfaction score was moderate (143.59 ± 26.86). Job satisfaction was higher in emergency call center personnel, high school graduates, and head nurses, working 40-50 hours a week, with seniority 1-4 years, and had integration training (p<0.05). Conclusion: Emergency healthcare personnel in Northern Cyprus are primarily nurses. Most of them have not received updated training recently. Studies in which most participants are paramedics will reflect the current situation more objectively. Therefore, structuring emergency health services as a separate unit within the Ministry of Health and the necessary regulations can increase job satisfaction even more.